2023
DOI: 10.3389/fpls.2023.1099589
|View full text |Cite
|
Sign up to set email alerts
|

Fertilizer source and application method influence sugarcane production and nutritional status

Abstract: IntroductionThe contrasting weather conditions throughout the sugarcane harvest period in south-central Brazil (April to November) influence fertilization management in sugarcane ratoon.MethodsThrough field studies carried out over two cropping seasons, we aimed to compare the performance of sugarcane at sites harvested in the early and late periods of the harvest season as a function of fertilizer sources associated with application methods. The design used in each site was a randomized block in a 2 x 3 facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Overexpression of these transcription factors can enhance the growth of Arabidopsis thaliana roots under low potassium stress (Hong et al, 2013). These studies demonstrated that the enhancing expression regulation of potassium transporter genes can increase the growth tolerance of plants during low potassium conditions (Castro et al, 2023).…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…Overexpression of these transcription factors can enhance the growth of Arabidopsis thaliana roots under low potassium stress (Hong et al, 2013). These studies demonstrated that the enhancing expression regulation of potassium transporter genes can increase the growth tolerance of plants during low potassium conditions (Castro et al, 2023).…”
Section: Introductionmentioning
confidence: 76%
“…Therefore, the key to achieving high sugarcane yield maintaining su cient nutrient supply. An adequate nutrient supply is crucial for high sugarcane yield (Li et al, 2011;Herrera et al, 2022;Castro et al, 2023). The HAK potassium transporter gene family is an important K + transporter that plays a major role in the absorption and transport of potassium in sugarcane.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the key to achieving high sugarcane yield maintaining su cient nutrient supply. An adequate nutrient supply is crucial for high sugarcane yield [1][2][3]. The HAK potassium transporter gene family is an important K + transporter that plays a major role in the absorption and transport of potassium in sugarcane.…”
Section: Introductionmentioning
confidence: 99%
“…Later integration with the BIN function of GACD software led to the selection of fewer simplex markers (459) than existing sugarcane markers (da Silva et al, 1995; LIU et al, 2010; Wang et al, 2022),and the total length of the genetic map established using high-quality simplex markers was 1578.04cM.The growth and development processes of sugarcane are affected by genotype, ecological environment, and other factors. To obtain phenotypic data as accurately as possible, eld management measures such as fertilization(Castro et al, 2023) and irrigation(Brauman & Viart, 2016) should be planned and implemented, and multi-environment planting is necessary for the experiment. On this basis, data on the growth of plants, tillers, and effective stalk phenotypes at the two test sites were collected over two years.…”
mentioning
confidence: 99%